2021
DOI: 10.1139/apnm-2020-0388
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thermal pasteurization on viral load and detectable live viruses in human milk and other matrices: a rapid review

Abstract: Holder pasteurization (62.5ºC, 30 min) of human milk (HM) is thought to reduce the risk of transmitting viruses to an infant. Some viruses may be secreted into milk – others may be contaminants. The effect of thermal pasteurization on viruses in HM has yet to be rigorously reviewed. The objective of this study is to characterize the effect of common pasteurization techniques on viruses in HM and non-HM matrices. Databases (MEDLINE, Embase, Web of Science) were searched from inception to April 20th, 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 115 publications
2
20
0
5
Order By: Relevance
“…However, our observations, combined with the negativity of human milk samples after Holder pasteurization confirmed by different authors (Pitino et al, 2020;Unger et al, 2020;Walker et al, 2020), support that donor human milk is a safe product, after carrying out an appropriate evaluation of donor mothers to obtain eligibility for the donation. To the best of our knowledge, our study is the first one to analyze human milk containers and milk samples from all donor mothers.…”
Section: Universal Screening For Sars-cov-2 Of All Human Milk Bank Sasupporting
confidence: 85%
See 1 more Smart Citation
“…However, our observations, combined with the negativity of human milk samples after Holder pasteurization confirmed by different authors (Pitino et al, 2020;Unger et al, 2020;Walker et al, 2020), support that donor human milk is a safe product, after carrying out an appropriate evaluation of donor mothers to obtain eligibility for the donation. To the best of our knowledge, our study is the first one to analyze human milk containers and milk samples from all donor mothers.…”
Section: Universal Screening For Sars-cov-2 Of All Human Milk Bank Sasupporting
confidence: 85%
“…Cold storage of SARS-COV-2 in human milk did not significantly change viral load over a 48 hr period according to a study in which the virus was experimentally inoculated into human milk samples (Walker et al, 2020). Nevertheless, SARS-CoV-2 is effectively inactivated by Holder pasteurization (62.5°C, 30 min) of human milk, if present (Pitino et al, 2020;Unger et al, 2020). These observations suggest that current human milk bank (HMB) processes would effectively reduce an eventual risk of transmission of respiratory viruses such as SARS-CoV-2 to most fragile neonates.…”
Section: Universal Screening For Sars-cov-2 Of All Human Milk Bank Samentioning
confidence: 99%
“…In conclusion, our data clearly confirm that the heat treatment for 30 min at 60°C guarantees the total inactivation of HCMV. Taking into account that previous reports suggest that this is also applicable to other breastfeeding transmitted viruses, like HIV, HTLV and Parvovirus B19 ( 16 , 17 ), we consider that this variant of Holder pasteurization may be a good compromise between the microbial inactivation and the preservation of nutritional properties using the same pasteurizer equipment found in most of Human Milk Banks. These aspects make the procedure of pasteurization favorable especially in low-income countries.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the aim of this work has been to evaluate the temperature sensitivity of HCMV during the processing of donor breast milk under the same conditions that are commonly used in human milk banks. If it is confirmed that HCMV is destroyed at temperatures lower than that used in Holder pasteurization, as shown in the literature for most infectious agents ( 16 , 17 ), the possibility of a thermal treatment of donated milk more respectful with its biological components would be possible and this would be beneficial for the receptors.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation